PHARMACOLOGICAL PROFILE OF VATSANABHA: VISHA DRUG: AMRITA GUNA - Deepa Jose,; Teresa Cyriac,; Rajarajeswari L.A,; Sahila T.S, (International Journal of Ayurveda and Pharma Research, 2020)
Vatsanabha (Aconitum ferox) belongs to a group of potential drugs called Mahavishas, belonging to the genus Aconitum, Family Ranunculaceae. It is widely distributed in North Eastern Himalayan region. Earlier Aconite was more understood as a poison than a medicine. The roots of Aconitum ferox known under the common name Vatsanabha is extremely poisonous but after their detoxification process the drug is useful in the treatment of diseases such as rheumatoid arthritis, fever, sciatic neuritis, hypertension and also act as immunomodulators. Aconitum alkaloid, when ingested mainly concentrates in the liver, kidney and serum and is eliminated through urine and faeces. As stated by Acharya Sushruta, Vatsanabha precipitates harmful effects such as yellow discoloration of stool, urine and eyes and neck stiffness. The diterpene alkaloids such as hypaconitine, aconitine, and mesaconitine are poisonous components present in the root tubers, which is converted into less toxic alkaloids such as aconine, benzoylaconine, and pyroaconine by alkaline treatment, heating or through deacetylation and oxidation reaction. The textbook ‘Rasaratna Samucchaya’ explains 8 stages of toxic effect of Aconitum ferox. Shodhana process can be defined as the removal of unwanted part of drug and eradication of highly toxic ingredients. In addition to its detoxification properties, the efficacy and potency of the drug can be increased by Shodhana process. Thin layer chromatography studies have shown that the poisonous substances like psudoaconitine and aconitine is converted into less poisonous substance like veratroyl pseudoaconine and benzoyl aconine respectively only in traditional Ayurvedic shodhana.